Experimental investigation and lumped kinetic modeling studies for upcycling of polyolefins - Kavade, Omkar G.; Dhepe, Paresh L.; Devi, Nandini R.; Vasireddy, Satyam Naidu (Journal of the Indian Chemical Society, 2025)
The present work discusses on comparative kinetic analysis of the pyrolysis of polypropylene (PP), high-density polyethylene (HDPE), and low-density polyethylene (LDPE) using sophisticated lumped models. Unlike many previous studies that focused on single-polymer kinetic models or employed simplified reaction schemes, this study develops an enhanced multistep reaction network that explicitly considers both primary decomposition and secondary cracking pathways, thereby improving the accuracy of product distribution predictions. By integrating this detailed reaction framework with a robust nonlinear regression approach using LSQNONLIN and ODE45 solvers in MATLAB, the study achieved greater accuracy in estimating kinetic parameters than traditional curve-fitting methods. The findings reveal that HDPE exhibits the highest activation energy (222.97 kJ mol(-1)), indicating it is more thermally stable than LDPE (193.44 kJ mol(-1)) and PP (62.16 kJ mol(-1)). One of the highlights of the present work is that lower pyrolysis temperature (400 degrees C) is found to be optimum for liquid yield by reducing secondary cracking, which aligns with the sustainable fuel production principles. The study also emphasizes on the limitations of previous lumped models that overlooked wax decomposition pathways, which are crucial for optimizing the hydrocarbon distribution. Future research should investigate catalytic interventions and reactor design modifications to enhance the product selectivity and scalability. This study offers a more comprehensive kinetic framework for advancing the valorization of plastic waste through pyrolysis, aiding the development of efficient waste-to-fuel conversion strategies.
Keywords: Lumped kinetic modeling; Plastic pyrolysis; Rate constants; Reaction pathways; Secondary cracking reactions; Temperature-dependent product distributions